Multiple intelligences and financial decisions: An exploration - Jean David Polo Vargas; María Esperanza Cuenca Coral; Andrés Felipe Zambrano Curcio; Miltón José Zambrano Curcio; Andrés Muñoz Alvis (Psicogente)
Objective: The objective of this research is to establish a relationship between the theory of multiple intelligences with the management and use of credit cards, including risk, patience, and economic education. This will allow the establishment of a line of marketing and consumption contextualized to the types of intelligence.